2010
DOI: 10.1021/bi902026v
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutations in Aedes aegypti Sterol Carrier Protein-2 on the Biological Function of the Protein

Abstract: Sterol carrier protein-2 (SCP-2) is a non-specific intracellular lipid carrier protein. However, the molecular mechanism of ligand selectivity and the in vivo function of SCP-2 remain unclear. In this study, we used site directed mutagenesis to investigate ligand selectivity and in vivo function of the yellow fever mosquito sterol carrier protein-2 protein (AeSCP-2). Mutations to amino acids in AeSCP-2 known to interact with bound ligand also decreased NBD-cholesterol binding. Substitution of amino acids in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 50 publications
4
18
0
Order By: Relevance
“…A. aegypti larval lipids reserve includes cholesterol [31] and deficiency in dietary cholesterol has lethal effects on A. aegypti larvae [30]. We have shown that AeSCP-2 selectively mediates cellular cholesterol uptake [18], [32]. It is possible that developing male larvae require the storage of much higher amount of cholesterol than that of females and AeSCP-2 mediated cholesterol uptake from the dietary sources becomes a much more critical factor for the survival of males.…”
Section: Discussionmentioning
confidence: 95%
“…A. aegypti larval lipids reserve includes cholesterol [31] and deficiency in dietary cholesterol has lethal effects on A. aegypti larvae [30]. We have shown that AeSCP-2 selectively mediates cellular cholesterol uptake [18], [32]. It is possible that developing male larvae require the storage of much higher amount of cholesterol than that of females and AeSCP-2 mediated cholesterol uptake from the dietary sources becomes a much more critical factor for the survival of males.…”
Section: Discussionmentioning
confidence: 95%
“…SCP2 encodes an intracellular sterol carrier protein that facilitates cholesterol uptake in Ae . aegypti cells [59]. Knockdown or chemical inhibition of SCP2 was recently shown to inhibit DENV replication in Ae .…”
Section: Discussionmentioning
confidence: 99%
“…Sterol carrier protein-2 (SCP-2) has been identified in several insect species 9,[30][31][32] and is thought to mediate cholesterol uptake and intracellular transportation. 9,11,12,33) Also, several chemical compounds that strongly inhibit the binding between cholesterol and AeSCP-2 (SCP-2 in Aedes aegypti) have been identified.…”
Section: Discussionmentioning
confidence: 99%